2005
DOI: 10.1111/j.1365-2362.2005.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood profiles, body fat and mood state in healthy subjects on different diets supplemented with Omega‐3 polyunsaturated fatty acids

Abstract: AA/EPA and mood state are differently influenced by diet and Omega-3, body fat is particularly reduced by Zone diet, while blood parameters such as triglycerides/HDL ratio, insulin and homocysteine are related to AA/EPA variations. These findings are discussed in terms of differences in the composition of the diets and the influences of Omega-3 on physiological functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 52 publications
(92 reference statements)
3
67
0
Order By: Relevance
“…Two studies, however, found no benefit of supplementation with EPA þ DHA (12) or E-EPA (116) for depression, mania or bipolar symptoms. All four studies involving volunteers with no diagnosis of depression also found no differences between treatment and placebo groups following supplementation with DHA (89) , EPA þ DHA (119) , EPA þ DHA þ other n-3PUFA (118) or advice to eat fish or supplementation with EPA (117) . Of the studies involving individuals with other psychiatric conditions, one study found a beneficial effect of EPA þ DHA compared with placebo on depression in chronic fatigue patients (120) , one study found a beneficial effect of E-EPA compared with placebo on depression in patients with borderline personality disorder (124) and one study found a benefit of EPA þ DHA compared with placebo on depression in individuals who self-harm (126) .…”
Section: Trial Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…Two studies, however, found no benefit of supplementation with EPA þ DHA (12) or E-EPA (116) for depression, mania or bipolar symptoms. All four studies involving volunteers with no diagnosis of depression also found no differences between treatment and placebo groups following supplementation with DHA (89) , EPA þ DHA (119) , EPA þ DHA þ other n-3PUFA (118) or advice to eat fish or supplementation with EPA (117) . Of the studies involving individuals with other psychiatric conditions, one study found a beneficial effect of EPA þ DHA compared with placebo on depression in chronic fatigue patients (120) , one study found a beneficial effect of E-EPA compared with placebo on depression in patients with borderline personality disorder (124) and one study found a benefit of EPA þ DHA compared with placebo on depression in individuals who self-harm (126) .…”
Section: Trial Evidencementioning
confidence: 99%
“…Of these studies, Behan et al (120) found decreases in fatigue following supplementation with EPA þ DHA compared with placebo in sixty-three individuals diagnosed with chronic fatigue syndrome, Fontani et al (118) found decreases following supplementation with EPA þ DHA compared with placebo in thirty-three healthy volunteers, and Yehuda et al (144) found decreases in fatigue following supplementation with ALA þ n-6PUFA compared with placebo in 126 individuals suffering from test anxiety. Benefits of n-3PUFA supplementation for individuals with chronic fatigue syndrome have also been reported in several individual cases (147) .…”
Section: Trial Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Maes et al [45] showed that major depression was associated with reduced eicosapentaenoic acid (EPA; 20:5n-3) and docosapentaenoic acid (DPA; 22:5n-3) fractions in phospholipids, reduced alpha-linolenic acid (ALA; 18:3n-3), EPA and total n-3 in cholesteryl esters and increased arachidonic acid (AA; 20:4n-6) to EPA ratio in both phospholipids and in cholesteryl esters. It has also been shown that depression is directly associated with increases in the ratios of n-6 PUFA to n-3 PUFA and of AA to EPA concentrations in plasma and erythrocytes [20,45,46].…”
Section: Discussionmentioning
confidence: 99%